Conformism and structural change - Takeo Horiy; Masako Ikefuji; Kazuo Mino (Osaka University, Institute of Social and Economic Research (ISER), 2011)
We study structural change in a simple, two-sector endogenous growth model and show that the presence of commodity-specific consumption externalities can be a source of structural change. When the degrees of consumption externalities are different between different goods, the two sectors grow at different rates, whereas the aggregate economy exhibits balanced growth in the sense that capital stock and expenditure grow at the same constant rate. Under the more restrictive condition such that the degrees of consumption externalities are the same, structural change does not occur. We also show that the dependence of the benchmark consumption levels on the past consumption is crucial for the divergent patterns of structural change across countries.
Keywords: E21; E30; O10; O41; 330; Structural change; Consumption externalities; Two-sector growth model; Kaldor facts; Strukturwandel; Nachfrageinterdependenz; Mehr-Sektoren-Modell; Neue Wachstumstheorie; Theorie